Cognitive--behavioural therapy and family intervention for relapse prevention and symptom reduction in psychosis: randomised controlled trial. - Garety, P; Fowler, D; Freeman, D; Bebbington, P; Dunn, G; Kuipers, E (2008)
BACKGROUND: Family intervention reduces relapse rates in psychosis. Cognitive-behavioural therapy (CBT) improves positive symptoms but effects on relapse rates are not established. AIMS: To test the effectiveness of CBT and family intervention in reducing relapse, and in improving symptoms and functioning in patients who had recently relapsed with non-affective psychosis. METHOD: A multicentre randomised controlled trial (ISRCTN83557988) with two pathways: those without carers were allocated to treatment as usual or CBT plus treatment as usual, those with carers to treatment as usual, CBT plus treatment as usual or family intervention plus treatment as usual. The CBT and family intervention were focused on relapse prevention for 20 sessions over 9 months. RESULTS: A total of 301 patients and 83 carers participated. Primary outcome data were available on 96% of the total sample. The CBT and family intervention had no effects on rates of remission and relapse or on days in hospital at 12 or 24 months. For secondary outcomes, CBT showed a beneficial effect on depression at 24 months and there were no effects for family intervention. In people with carers, CBT significantly improved delusional distress and social functioning. Therapy did not change key psychological processes. CONCLUSIONS: Generic CBT for psychosis is not indicated for routine relapse prevention in people recovering from a recent relapse of psychosis and should currently be reserved for those with distressing medication-unresponsive positive symptoms. Any CBT targeted at this acute population requires development. The lack of effect of family intervention on relapse may be attributable to the low overall relapse rate in those with carers.